Treatment for non-tuberculous mycobacteria: challenges and prospects - Conyers, Liberty E.; Saunders, Bernadette M. (Frontiers in Microbiology, 2024)
Non-Tuberculous mycobacteria (NTM) are opportunistic environmental bacteria. Globally, NTM incidence is increasing and modeling suggests that, without new interventions, numbers will continue to rise. Effective treatments for NTM infections remain suboptimal. Standard therapy for Mycobacterium avium complex, the most commonly isolated NTM, requires a 3-drug regime taken for approximately 18 months, with rates of culture conversion reported between 45 and 70%, and high rates of relapse or reinfection at up to 60%. New therapeutic options for NTM treatment are urgently required. A survey of ongoing clinical trials for new NTM therapy listed on ClinicalTrials.Gov using the terms ‘Mycobacterium avium’, ‘Mycobacterium abscessus’, ‘Mycobacterium intracellulare’, ‘Non tuberculous Mycobacteria’ and ‘Nontuberculous Mycobacteria’ and a selection criterion of interventional studies using antibiotics demonstrates that most trials involve dose and combination therapy of the guideline based therapy or including one or more of; Amikacin, Clofazimine, Azithromycin and the anti-TB drugs Bedaquiline and Linezolid. The propensity of NTMs to form biofilms, their unique cell wall and expression of both acquired and intrinsic resistance, are all hampering the development of new anti-NTM therapy. Increased investment in developing targeted treatments, specifically for NTM infections is urgently required.